2019
DOI: 10.1007/s10585-019-10015-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic artery infusion pump for nasopharyngeal carcinoma with liver metastasis

Abstract: To evaluate the benefits and risks of hepatic artery infusion (HAI) gemcitabine and floxuridine (FUDR) in patients with nasopharyngeal carcinoma liver metastases. HAI catheter systems were implanted under the guide of digital subtract angiography (DSA) in 16 patients with unresectable nasopharyngeal carcinoma liver metastases. HAI gemcitabine and FUDR in combination with radiotherapy and systemic chemotherapy were delivered. Disease control rate (DCR) of intrahepatic lesions is 100%, objective response rate (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 28 , 45 , 46 RFA for treating NPC patients with 1–3 LiMs prolongs survival compared to those who only receive chemotherapy (median OS: 48.1 versus 25.9 months). 47 Peng et al 48 reported the effectiveness of TACE for NPC patients with LiM, and they suggested that it can be optional for suitable patients because it may control intrahepatic lesions and prolong survival. The advantage of RT, especially stereotactic body radiation therapy, is that its effectiveness is not impaired by intravascular blood flow or bile accumulation in the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 45 , 46 RFA for treating NPC patients with 1–3 LiMs prolongs survival compared to those who only receive chemotherapy (median OS: 48.1 versus 25.9 months). 47 Peng et al 48 reported the effectiveness of TACE for NPC patients with LiM, and they suggested that it can be optional for suitable patients because it may control intrahepatic lesions and prolong survival. The advantage of RT, especially stereotactic body radiation therapy, is that its effectiveness is not impaired by intravascular blood flow or bile accumulation in the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…For HAI therapy, many research studies prefer surgery rather than radiological procedure to implant HAI pump system ( 11 , 14 ), due to concerns about frequent dislodgement and extrahepatic infusion related to radiologically implanted catheter. In fact, these shortcomings of radiological procedure may be overcome by introducing modified techniques ( 12 , 15 , 28 , 29 ). First, the rate of catheter displacement could be reduced to less than 5% by “tip-fix” technique ( 28 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“… 11 - 13 In addition, HAI chemotherapy has also been suggested to be helpful for patients with NPC liver metastasis, but a few patients had extrahepatic progression during the trial treatment. 15 In this study, we administered HAI gemcitabine plus FUDR combined with systemic chemotherapy for 19 patients with BCLM. The overall response rate (ORR) of intrahepatic lesions was 73.7%.…”
Section: Discussionmentioning
confidence: 99%
“…The infusion catheter and injection port (Celsite, B. Braun, Chasseneuil, France) were implanted as previously described. 12 , 15 , 16 The main steps of this procedure include the following: (a) The anatomy of the hepatic artery and indication for HAI therapy were evaluated by computed tomography angiography before the operation; (b) the Seldinger technique was used to obtain access to the right femoral artery under the guide of digital subtract angiography (DSA); (c) angiography of the celiac trunk and superior mesenteric artery was performed to reveal the anatomy of the hepatic artery; (d) the gastro-duodenal artery (GDA), right gastric artery, and, if necessary, left gastric artery or dorsal pancreatic artery were embolized using metallic coils (Tornade, Cook, Bloomington, IL, USA) to prevent gastrointestinal mucosa injury caused by chemotherapy drugs; (e) the infusion catheter with side holes was placed into the GDA using the same coils as mentioned above or was inserted into the peripheral branch of the hepatic artery, and the position of the side hole was sited at the common hepatic artery. Therefore, the chemotherapeutic agents infused the entire liver from the side hole; (f) the proximal end of the infusion catheter was connected to an injection port, and the device was implanted into a subcutaneous pocket in the right inner thigh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation